PRAKTIK MAKELAR DALAM JUAL BELI MOBIL BEKAS DI MGC GARAGE MADIUN DITINJAU DARI PERSPEKTIF ISLAM - Morgana, Iqrok Glady; Rachmawati, Lucky (Universitas Negeri Surabaya, 2021)
A broker is a trade intermediary between a seller and a buyer who must have buying and selling practices according to Islamic law so that the contract is valid and does not prohibit actions that are prohibited. The purpose of this study is to see and understand the practice of buying and selling used cars at MGC Garage Madiun from an Islamic legal perspective. The research approach was descriptive qualitative. Data collection through in-depth interviews, observation, and documentation. Data were collected at the MGC Garage Madiun showroom with showroom owners, brokers and buyers. The results of this study explain that the practice of buying and selling used cars by brokers at MGC Garage is generally in accordance with the principles of Islamic business ethics, including the principles of tawhid, help, honesty, trust, mutual agreement (pleasure), transparency, and responsibility. The practice of brokerage has also fulfilled the pillars and legal requirements of buying and selling in Islam. However, the improvement of payment methods from conventional banks to Islamic banks so that contract transactions from an Islamic perspective run perfectly.